2018
DOI: 10.3390/ijerph15081580
|View full text |Cite
|
Sign up to set email alerts
|

Age, Period, and Cohort Effects on Suicide Mortality in South Korea, 1992–2015

Abstract: Although the effects of age, period, and cohort (APC) on suicide are important, previous work in this area may have been invalid because of an identification problem. We analyzed these effects under three different scenarios to identify vulnerable groups and thus overcame the identification problem. We extracted the annual numbers of suicides from the National Death Register of Korea (1992–2015) and estimated the APC effects. The annual average suicide rates in 1992–2015 were 31.5 and 14.7 per 100,000 males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In the younger age group, the majority of patients were women, whereas in the older adult group, the majority of patients were men. Some researchers have demonstrated a correlation between age increase and suicide death rate [20,21]. Of course, other factors also increase suicide mortality in old age, such as social isolation and poor physical or financial conditions [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the younger age group, the majority of patients were women, whereas in the older adult group, the majority of patients were men. Some researchers have demonstrated a correlation between age increase and suicide death rate [20,21]. Of course, other factors also increase suicide mortality in old age, such as social isolation and poor physical or financial conditions [22].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, potential interventions aimed at ameliorating the individual and societal costs of mental health problems could be targeted at various life‐cycle periods. Indeed, age seems to play a particularly important role in mental health problems and a host of studies have investigated the age‐pattern of mental health (Bell, 2014 ; Blanchflower & Oswald, 2008 , 2016 ; Kino et al., 2019 ; Lang et al., 2011 ; Le Bon & Le Bon, 2014 ; Okui, 2020 ; Page et al., 2013 ; Park et al., 2018 ). The majority of these studies have found that mental health follows a U‐shaped pattern in age: young and old individuals generally experience better levels of mental health than individuals in, or close to, middle age (Blanchflower & Oswald, 2008 , 2016 ; Lang et al., 2011 ; Le Bon & Le Bon, 2014 ; Okui, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 2019 ), Park et al. ( 2018 ), and Okui ( 2020 ), relying on assumptions around the linear period or cohort trend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além da subnotificação, a qualidade dos dados associados ao suicídio também pode Na literatura internacional, há crescente interesse por análises de idade-período-coorte para o estudo da mortalidade por suicídio. Além dos estudos descritivos que focam exclusivamente em análises gráficas (Gunnell et al, 2003;Dougall et al, 2017), há publicações com modelagens estatísticas de efeitos idade-período-coorte para analisar o fenômeno do suicídio em países da Ásia (Park et al, 2016;Park et al, 2018;Kino et al, 2019), da Europa (Jukkala et al, 2017;Parkison et al, 2017;Doğan et al, 2019), nos Estados Unidos da América (Phillips, 2014;Wang et at., 2016) e em perspectiva internacional, comparando países ricos (Chauvel et al, 2016). No entanto, essa abordagem parece não ter sido utilizada ainda no Brasil quando se analisam os óbitos autoprovocados, exceto por um estudo sobre o Estado do Rio de Janeiro (Rodrigues e Werneck, 2005).…”
Section: Introductionunclassified